The Reader at Play in “Auggie Wren’s Christmas Story” by Paul Auster - Linda Collinge-Germain (Transatlantica)
Michel Picard, in an interdisciplinary approach using existing research in the fields of psychology and anthropology, theorized the link between the literary reader and play in his essay La Lecture comme jeu published in 1986. His hypothesis is that reading is a specific form of play and like play has a function. Though Paul Auster, in spite of his spending several years in France, most probably had no contact with Picard’s essay, his story “Auggie Wren’s Christmas Story,” published on December 25, 1990 in The New York Times, seems, uncannily, nearly an illustration of the theory of “Reading as Play” as both in its form and its content the story problematizes the dialectics of participation and distancing inherent in the literary reading process defined by Picard.